A plain & simple heart - Copeland, Lori (Copeland, Lori. Amish of Apple Grove, 2012)
Young Amish woman Rachel Switzer comes to 1880s Lawrence, Kansas in pursuit of cowboy Jesse Montgomery, only to be caught in the middle of a temperance riot and mistakenly arrested by sheriff Colin Maddox.